The dawn of the Arab uprisings : end of an old order? - Haddad, Bassam; Bsheer, Rosie; Abu-Rish, Ziad. (London : Pluto Press ; New York, NY : Distributed in the United States of America exclusively by Palgrave Macmillan, 2012)
"The Dawn of the Arab Uprisings sheds light on the historical background and initial impact of the mass uprisings which have shaken the Arab world since December 2010. The book brings together the best writers from the online journal Jadaliyya, which has established itself as an unparalleled source of information and critical analysis on the Middle East. The authors, many of whom live in the countries affected, provide unique understanding and first-hand accounts of events that have received superficial and partial coverage in Western and Arab media alike. While the book focuses on those states that have been most affected by the uprisings it also covers the impact on Jordan, Saudi Arabia, Lebanon, Palestine, and Iraq. The Dawn of the Arab Uprisings covers the full range of issues involved in these historic events, from political economy and the role of social media, to international politics, gender, labour and the impact on culture, making this the ideal one-stop introduction to the events for the novice and specialist alike."--Publisher's website.
Introduction - The Arab Uprisings: Unmaking of an Old Order? -- Section I: Opening Posts 1. Historical Observations on the Arab Revolutions of 2011/ Rashid Khalidi ; American Narratives About the Arab Spring / Jillian Schwedler. -- Section II: Tunisia. Initial Reflections / Mohammed Bamyeh ; Tunisia's Glorious Revolution / Noureddine Jebnoun. -- Section III: Egypt. The Poetry of Revolt / Elliott Colla ; The Facebook Factor / Linda Herrera ; International Aid and Structural Adjustment / Adam Hanieh. -- Section IV: Libya. The Arabs in Africa / Callie Maidhof ; Myths and Realities in the Battle for Misrata / Jamila Benkato. -- Section V: Bahrain. Let's Talk About Sect / Tahiyya Lulu ; The Bahraini Opposition's Struggle for Survival / Rosie Bsheer. -- Section VI: Yemen. How it Started in Yemen: From Tahrir to Taghyir / Nir Rosen ; Saleh Defiant / Ziad Abu-Rish. -- Section VII: Syria. Why Syria Is Not Next .. So Far / Bassam Haddad ; Syrian Hope: A Journal / Amal Hanano. -- Section VIII: Regional Reverberations of the Arab Uprisings. The Status Quo and Protests in Jordan / Ziad Abu-Rish ; Saudi Arabia's Silent Protests / Rosie Bsheer ; Protests and Constitutions in Morocco / Emanuela Dalmasso ; Algeria and the Politics of Memory / Muriam Haleh Davis ; Iraq and Its Tahrir Square / Zainab Saleh. -- Section IX: Conclusion.
Includes bibliographical references (p. 286-296) and index.
Keywords: Protest movements -- Arab countries -- History -- 21st century; Democratization -- Arab countries -- History -- 21st century; Arab countries -- Politics and government -- 21st century